Between government unilateralism and corporatist bargaining: public sector pension reforms in the UK and Ireland, 2000s–2010s. (22nd April 2019) - Park, Sung Ho
Abstract: Studies on welfare reform in advanced European countries have identified two established paths to welfare retrenchment: government unilateralism and corporatist bargaining. This study explores a more complicated path to welfare reform, wherein governments pursue 'non-corporatist' bargaining by actively combining features of unilateralism and negotiation. Such a hybrid case is explained by employing an 'insider-outsider' framework for public policy reform. The key argument is that the presence of exclusive insiders complicates the reform process, disqualifying both unilateralism and corporatist bargaining as feasible options for benefit cuts. The author demonstrates the validity of this claim by examining three cases of public sector pension retrenchment in the UK and Ireland during the 2000s and 2010s. Defying the common expectation that benefit cuts in residual welfare states would be promoted with government unilateralism, the public sector pension reforms in the UK and Ireland exhibited more complicated features which combined governments' unilateral initiatives and ad hoc negotiations with public sector unions. Future studies may build on this finding to examine hybrid reform cases in a general European context.